Neuromuscular bandage for the prevention of post-mastectomy seroma: a clinical trial protocol - Fabro, Erica Alves Nogueira; Costa, Rejane Medeiros; Macedo, Flávia Oliveira; Torres, Daniele Medeiros; Aguiar, Suzana Sales de; Thuler, Luiz Claudio Santos; Bergmann, Anke (Mastology, 2024)
Introduction: Seroma is the most common early complication after breast cancer surgery and is associated with other complications and adjuvant therapy delays. A potential hypothesis for its prevention is the obliteration of dead space between tissues, which can be achieved by external compression. To assess whether the use of a neuromuscular bandage employing the compressive technique during the first postoperative week is effective in preventing seroma. Methods: This study comprises a two-arm randomized superiority clinical trial to evaluate the following as primary outcomes: seroma incidence, volume and duration using a suction drain and bandage safety and satisfaction as secondary outcomes. Women aged ≥18 years submitted to a mastectomy as breast cancer treatment will be included, while women submitted to bilateral mastectomies, immediate breast reconstruction or surgical flap rotation closure, who present hematomas or surgical wound infections at the time of recruitment or autoimmune diseases that lead to skin lesions and/or allergy to tape, as well as those exhibit difficulties in understanding the study will be excluded. Randomization will be performed by lots at study enrollment. Coded envelopes will be available for intervention or control group allocations. Patients allocated in the intervention group will be submitted to the bandage application for seven days. All patients will use a suction drain according to the institution’s routine. Ethics and disclosure: This study was approved by the Brazilian National Cancer Institute, Research Ethics Committee under no. 2,774,824 and it is registered in the ClinicalTrials.gov (NCT04471142).